Art Educators' Thrift Shopping Practices as Social Action. (2nd October 2019) - Hochtritt, Lisa
Abstract : How do artists and art educators who are engaged in regular thrifting view their consumptive practices? In this article, I draw on a small pilot case study and interview data from five artist–educators living in the southwestern United States and examine the motivations and habits of their thrift shopping practices. Findings shared by participants elucidate their conscious decisions to prioritize the purchase of secondhand goods and personal stories linked to the objects. Five themes about thrift shopping habits emerged from the data: (1) linked to personal identity; (2) utilitarian; (3) activism; (4) objects hold meaning; and (5) thrifting promotes feelings and actions related to relaxation and pleasure. Results conclude that artists and art educators view thrift shopping and consumer culture as a personal, interventionist practice that questions social norms. They also recast thrift shopping as a place of collaborative social practice in which participants have the power to individualize consumption.